Application of Fuzzy Logic for Presentation of an Expert Fuzzy System to Diagnose Thalassemia - Thakur, S; Raw, SN; Prakash, A; Mishra, P; Sharma, R (International Journal of Computer Sciences and Engineering, 2025)
In this paper We have designed a Thalassemia diagnosis model under some fuzzy rules. The performance of the system is approximately similar as the clinical results. Also, through this system the category of Thalassemia disease can be predictable. We have used MATLAB tool of Mamdani Fuzzy Inference System (FIS) to identify the severity of the disease. The objective of this research is to create a Fuzzy model for Thalassemia disease diagnosis. The results in this work can be obtained by a simple and inexpensive method. This would generate, in economic terms, significant savings.